Impact of public transport strikes on the road network: The case of Athens. (February 2020) - Spyropoulou, Ioanna
Abstract: Public transport strikes comprise a form of traffic disruption affecting "normal" traveller behaviour, and result in the increase of traffic congestion, traffic accidents and air pollution. Travellers modify their trip characteristics in anticipation of strike effects, while their behaviour depends on various factors including individual characteristics, trip flexibility, available transport modes and attitudes towards them. This study explores the effect of public transport strikes on traffic conditions utilising loop detector data and, in particular, examining the impacts on traffic flow, mean speed and travel time. The city of Athens is used as a reference case. The analysis employs descriptive statistics, as well as the design of generalised linear models to capture the impact of public transport strikes on traffic conditions, and to define the contributing spatio-temporal factors affecting the impacts. Study results highlighted the increase of congestion as expressed through all explored indicators, as a result of the strikes. In particular, increased traffic flow (up to 30%), reduced mean speed (up to 27%) and increased travel times (up to 25%) were observed at the majority of the explored sites. Public transport strike coverage and time of day were found to be the dominant factors. Other contributing factors were found to be day of the week and site-specific characteristics including: the existence of tolls; site location relative to the centre of Athens; and the existence of traffic lights on the explored links. The results of this study can form the basis for the design and implementation of targeted countermeasures that mitigate congestion effects, as well as measures promoting green transport resulting in travellers adopting more sustainable trip routines in the city of Athens.